Evaluation study of the National Immunization Program Information System - Brener Santos Silva; Hiago Victor Coelho; Ricardo Bezerra Cavalcante; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To carry out the National Immunization Program Information System (SIPNI) accessability assessment (EA), considering the description of the intervention, the elaboration of the theoretical-logical model and the identification of the evaluative questions. Method: A single case study with a qualitative approach, based on the system of seven elements proposed by Thurston and Ramaliu (2005). The SIPNI and the context of analysis, the vaccination rooms, were defined as the case. Results: The SIPNI description, based on documents and scientific evidence, made it possible to understand its operationalization, the main events that characterize it. The theoretical-logical model visually and systematically configured the SIPNI organization with details of the inputs, activities, products and expected effects. The evaluative questions were evaluated and validated to evaluate the SIPNI. Final considerations: The SIPNI is evaluable and presented a favorable scenario for its development. EA is an important strategy for planning subsequent evaluations, maximizing their potentials.